Body Composition, Muscle Strength, and Physical Function of Patients with Bethlem Myopathy and Ullrich Congenital Muscular Dystrophy. (12th September 2013) - Miscione, Maria Teresa; Bruno, Francesca; Ripamonti, Claudio; Nervuti, Giuliana; Orsini, Riccardo; Faldini, Cesare; Pellegrini, Massimo; Cocchi, Daniela; Merlini, Luciano
Abstract : Objective. To determine the contributions of body mass, adiposity, and muscularity to physical function and muscle strength in adult patients with Bethlem myopathy (BM) and Ullrich congenital muscular dystrophy (UCMD). Materials and Methods. Evaluation involved one UCMD and 7 BM patients. Body composition was determined by body mass index (BMI) and dual-energy-X-ray-absorptiometry (DXA), muscle strength by dynamometry, physical function by the distance walked in 6 minutes (6MWD), forced vital capacity (FVC) by a spirometer. Results. Six participants were of normal weight and 2 overweight based on BMI; all were sarcopenic based on appendicular fat free mass index (AFFMI); and 7 were sarcopenic obese based on AFFMI and % fat mass. Average muscle strength was reduced below 50% of normal. The 6MWD was in BM patients 30% less than normal. FVC was reduced in 4 of the BM patients. Muscle strength had a good correlation with the physical function variables. Correlation between muscle strength and BMI was poor; it was very high with AFFMI. AFFMI was the best single explicator of muscle strength and physical function. Conclusion. Muscle mass determined by DXA explains most of the variability of the measures of muscle strength and physical function in patients with BM and UCMD.